2020
DOI: 10.3389/fped.2020.00105
|View full text |Cite
|
Sign up to set email alerts
|

Volume Guarantee High-Frequency Oscillatory Ventilation in Preterm Infants With RDS: Tidal Volume and DCO2 Levels for Optimal Ventilation Using Open-Lung Strategies

Abstract: High frequency oscillatory ventilation with volume-guarantee (HFOV-VG) is a promising lung protective ventilator mode for the treatment of respiratory failure in newborns. However, indicators of optimal ventilation during HFOV-VG mode are not identified yet. In this study, we aimed to evaluate optimal high-frequency tidal volume (VThf) and the dissociation coefficient of CO 2 (DCO 2 ) levels to achieve normocapnia during HFOV-VG after lung recruitment in very low birthweight infants with respiratory distress s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 22 publications
0
20
1
Order By: Relevance
“…Infants in our sample also had a lower birth weight (728 vs. 882 g and 1100 g) and gestational age than in previous studies (25 vs. 27 and 28 weeks 12,13 ). Compared to those conventionally ventilated, we found that HFOV ventilated newborns also had a lower gestational age and birth weight.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Infants in our sample also had a lower birth weight (728 vs. 882 g and 1100 g) and gestational age than in previous studies (25 vs. 27 and 28 weeks 12,13 ). Compared to those conventionally ventilated, we found that HFOV ventilated newborns also had a lower gestational age and birth weight.…”
Section: Discussioncontrasting
confidence: 43%
“…The chart includes all patients ventilated with HFOV during the first 72 h of life. HFOV, high-frequency oscillatory ventilation; w, weeks T A B L E 1 Epidemiological characteristics of the 116 patients included in the study and subgroup characteristics for different frequency groups median volume of 1.93 ml/kg, and Tuzun et al 13 published data from 53 neonates with frequencies of 10 and 12 Hz and a median volume of 1.65 and 1.50 ml/kg, respectively. Unlike these authors, we analyzed data limited to infants with adequate ventilation, and we limited our sample to preterm newborns HFOV-ventilated before 72 h of life, since ventilation could change with lung inflammation and development during the first days of life.…”
Section: Discussionmentioning
confidence: 99%
“…18 At present, the initial value of VThf commonly applied in clinical practice is generally 1.5-2.0 ml/kg, while the target VThf range used in our study was 2-2.5 ml/kg, with an initial setting of 2 ml/kg. 7,9,19 This is because infants with congenital heart disease often have pulmonary edema and atelectasis after surgery, so they need a higher volume support to maintain normocapnia. Further research is needed to investigate whether these VThf target values change with age, body weight, or underlying disease.…”
Section: Discussionmentioning
confidence: 99%
“…Software algorithms adapt the applied pressure (to a set maximum peak pressure) to the exhaled tidal volumes of the last couple of inflations in order to achieve an expiratory tidal volume matching the set volume as closely as possible [ 87 ]. Targeted tidal volumes are usually set to 4–6 mL/kg in conventional ventilation [ 87 ] and 1 to 2 mL/kg for HFOV [ 88 ].…”
Section: What Is the Evidence For?mentioning
confidence: 99%